Optimization Design of Space Camera Enclosure Based on Bionics - Hongyu Li; Fu Li; Zhihua Zhao; Janfeng Yang; Juan Lv (Applied Sciences)
To optimize the design of the space camera enclosure, this paper employs biomimicry methods. The study compares the structural characteristics of the tendons and veins of the Victoria lindl, analyzes the similarities between the reinforced tendons and the Victoria lindl structure, and explores the feasibility of biomimicry design. An evaluation factor set and judgment matrix are established for both, and a similarity evaluation is conducted. Utilizing the Solidworks-Ansys interface, parametric modeling is performed, completing the biomimetic initial structural design of the space camera enclosure. Incorporating response surface optimization design principles, the study examines the relationship between the dimensions of stiffener and substrates, the maximum deformation of the enclosure, and the first-order natural frequency. Genetic algorithms are employed for optimization, leading to a secondary optimization design for the space camera enclosure. Through Ansys simulation analysis, a comparison is made between the first-order natural frequency, maximum deformation, and enclosure weight of the space camera enclosure before and after optimization. The results indicate that the biomimicry-inspired space camera enclosure structure, modeled after the tendons of Victoria lindl, can reduce weight by 36.9% compared to traditional designs, while maintaining high stiffness and fundamental frequency. This offers a novel approach for research in this field.